2007
DOI: 10.1007/s10620-006-9646-7
|View full text |Cite
|
Sign up to set email alerts
|

Oral Erythromycin Accelerates Impaired Gastrointestinal Motility After Endoscopic Mucosal Resection

Abstract: Gastrointestinal motility may be impaired after endoscopic mucosal resection of gastric lesions. We investigated whether oral erythromycin could improve motility. Twenty patients were divided randomly into groups that received oral omeprazole with or without erythromycin. Motility was recorded overnight at 3 days before and 4 days after endoscopic resection using a microtransducer probe. In the group without erythromycin, gastric phase III activity decreased significantly after endoscopic resection, while it w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…Gastric emptying is reduced in patients with gastric ulcers 10 11 12 . As in our study, delayed gastric emptying after endoscopic treatment was reported by Kawamura et al at 4 days after endoscopic mucosal resection 13 and by Uehara et al at 6 to 8 days after ESD 3 . Higuchi et al reported preserved gastric emptying at 8 weeks after ESD 4 .…”
Section: Discussionsupporting
confidence: 87%
“…Gastric emptying is reduced in patients with gastric ulcers 10 11 12 . As in our study, delayed gastric emptying after endoscopic treatment was reported by Kawamura et al at 4 days after endoscopic mucosal resection 13 and by Uehara et al at 6 to 8 days after ESD 3 . Higuchi et al reported preserved gastric emptying at 8 weeks after ESD 4 .…”
Section: Discussionsupporting
confidence: 87%
“…Gastric motility function is known to be temporarily decreased after gastric ESD. 23,24 Although there is no report of motility dysfunction after duodenal ESD, it is possible that a large resection size causes motility dysfunction, which may contribute to 25 but since we used lidocaine injection in all cases and found no difference in the rate of antispasmodic use, it seems that the ESD procedure itself has a strong effect on decreasing peristalsis. Underwater EMR (U-EMR) is a method that fills the gastrointestinal tract with saline during mucosal resection similar to WP-ESD.…”
Section: Discussionmentioning
confidence: 81%
“…However, in WP‐ESD, oral regurgitation may occur regardless of the resection time. Gastric motility function is known to be temporarily decreased after gastric ESD 23,24 . Although there is no report of motility dysfunction after duodenal ESD, it is possible that a large resection size causes motility dysfunction, which may contribute to liquid stagnation and oral regurgitation.…”
Section: Discussionmentioning
confidence: 99%
“…Third, we assessed gastric emptying only in patients with healed ESD‐induced gastric ulcers, not in patients with acute stage ulcers. Because gastric motility was reported decreased in patients in the acute stage of artificial gastric ulcers induced by conventional EMR, further studies are required to determine whether ESD affects gastric motility during the acute stage of artificial gastric ulcers. Fourth, although our linear regression analysis showed no relationship between gastric emptying and the size of the resected lesion, samples larger than 20 cm 2 were removed from only two of our patients.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear, however, whether ESD affects gastric motility functions. Although conventional EMR was shown to have minimal effects on gastric motility, ESD may affect gastric motility because it usually involves the resection of larger specimens than conventional EMR. We therefore investigated the effects of ESD on gastric motility in EGC patients by using the 13 C‐octanoic acid breath test to estimate gastric emptying.…”
Section: Introductionmentioning
confidence: 99%